Teodor Llorente, cinquanta anys després: Una polèmica entre Joan Fuster i Josep M. Bayarri. - CANO MATEU, J. ÀNGEL (Scripta, 2019)
This paper analyses the controversy that Joan Fuster and Josep M. Bayarri create on the Valencian press in 1961, as a result of the fifty years after Teodor Llorente's death. Whereas Fuster demands an intellectual discussion about the leader of the Renaixença in Valencia and the Valencian writers, Bayarri settles for commemorations and celebrations, masses, poetry readings or journal articles about him. This dialectic confrontation conceals two totally opposed ways of understanding the Valencianism of the postwar period. On the one hand, there is a Valencianism that proposes a self-criticism and a reflection; on the other hand, we find a Valencianism or an irrational «regionalism» that is sentimentalist and anti-intellectual. Therefore, this essay analyses the points of view about Llorente made by these two authors.